Factors Affecting the Participation of Non-governmental Organizations in Flood Crisis Management in Iran: A Qualitative Study - Alireza Sanatkhah (دانش پیشگیری و مدیریت بحران)
Background and objective The role of public participation in managing natural crises, including floods, is evident, and the government will incur many costs without utilizing the potential of non-governmental organizations (NGOs). This study aims to explore the perceptions of NGOs in Iran regarding public participation in flood relief during the 2020 flood in Chabahar city, Sistan & Baluchistan Province, south of Iran. Method This is a qualitative study using the grounded theory. Participants were 25 members of NGOs who participated in relief operations during the 2020 flood in Chabahar city, who were selected using a purposive sampling method. A semi-structured interview was used to collect data. Member checking, analytical comparisons, and the auditing technique were used to determine the trustworthiness of the data. The data were analyzed using the grounded theory approach in three stages: open coding, selective coding, and axial coding. Results Causal factors included: Formation and support of NGOs, quality of flood management, operational transparency, and media culture-building. The intervening factors included: Quality and manner of information dissemination, quality of relief goods distribution and relief services, quality of institutional trust, and social-cultural conflicts. Contextual factors included: Regional public support for relief groups, cultural structure, and professional ethics of relief groups. Strategies included: Education and information on relief efforts, pragmatic/revolutionary approach to flood management, establishment of participatory platforms, and utilization of capacities. Consequences included: Lack of coordination in flood management, inapplicable policies, personal-psychological consequences, and institutional distrust. Conclusion Various causal, intervening, and contextual factors influence public participation in managing crises caused by floods in Iran.